Empowering sustainable industrial 4.0 systems with machine intelligence - Ahmad, Muneer, 1977-; Jhanjhi, Noor Zaman, 1972- (Advances in logistics, operations, and management science (ALOMS) book series., 2022)
"This book addresses a wide range of topics related to industry 4.0 issues, its challenges and employment of smart and intelligent solutions to contain the errors and their impacts affecting stakeholders of such systems including, health industry, pharmaceutical industry, education industry, defense systems, manufacturing industry, logistic support systems, supply chain management, social media industry, and disaster management systems etc"--